(untitled) (Вісник: Міжнародні відносини, 2024)
The article examines the actualization of the Taiwan problem against the background of the full-scale Russian-Ukrainian war. The interests that determine the importance of Taiwan in the system of national priorities of the People’s Republic of China are analyzed. The key features of Beijing’s policy of establishing control over the island are highlighted.